Digital Transformation in Early Childhood Education Units with Limited Access to Digital Resources - Wariningsih, Tri; Najiha, Nihayatun (THUFULA, 2025)
This research generally aims to analyze digital transformation in Formal PAUD units, namely Kindergarten  with the limitations of digital technology. This research departs from three reasons, namely, technology plays an important role in supporting learning in the digital era, including in Formal Early Childhood Education, not all Formal Early Childhood education institutions have adequate digital technology resources and there is a significant gap between Formal Early Childhood Education institutions in urban areas and rural areas in terms of access to technology, institutions in urban areas are easier to obtain technological resources,  Meanwhile, institutions in rural areas are still very limited. The approach and method in this study are qualitative descriptive. Data collection was carried out through observation and interviews with 4 Formal PAUD institutions, consisting of 4 Kindergarten Principals and 4 Kindergarten teachers in Bansari District, Temanggung Regency. From the results of the study, it was found that there are limitations in digital technology infrastructure faced by Formal PAUD units in the highland rural areas of Temanggung Regency, the gap in access to digital technology. This greatly affects the quality of learning and digital competence of teachers in the Formal PAUD unit in the rural highland area of Temanggung Regency.